ELABORACIÓN DE UN PLAN DE MARKETING PARA LA EMPRESA DE POLLOS SANDI DE LA CIUDAD DE LOJA - Cárdenas Saritama, Luis Andrés (2016)
SANDi, is a company dedicated to the production and marketing of roasted chickens, products are offered to multiple customers that are denominated in any type of category and age, provides services and products in the lines Roasted chicken, potatoes Salchi, Carnes roasted, in the city of Loja. Chickens Sandi has no marketing plan so we feel the need for one to improve your customer acquisition and product marketing. The present work was developed with the aim of contributing to the administrative management of the company Chickens Sandi, in order to increase sales, market share, and become more competitive performing "DEVELOPMENT OF A MARKETING PLAN FOR THE COMPANY SANDI CHICKEN OF THE CITY OF LOJA ". This work was done with the help of instruments of data collection such as surveys and interviews with the manager and employees of the company, as well as gathering information on websites which allowed us to comfort and precision when choosing contents of the thesis. The research is focused on identifying some relevant aspects in the company so that they can give alternative solutions to strengthen its image, quality of service and therefore be more competitive in the market. The outcome of the Marketing Plan internal and external analysis Sandi Company details: SWOT analysis that contributed to the General structuring Marketing Plan was conducted, which proposed to implement promotional programs detailed, plan advertising and personnel training; where we plant the support and gratitude of social networks and web pages that are powerful for everyone and great choice of massive free publicity. Where we can come and interactive maps always used by tourists which can display options as offered 5 by our company services and products, consumer sites and phone numbers, photos of our products. Concluding that the company chickens Sandi Loja city does not have a marketing plan and advertising is not governed by previous studies. Our plan we seek to guide and improve marketing, according to what our company pursues.